Asuhan Akupunktur Pada Klien Sinusitis di Rumah Sehat “Ah” Bekasi - Yanti Angela Wisudha; Puspo Wardoyo; Chantika Mahadini; Amal Prihartono (Universitas Malahayati Lampung, 2026)
ABSTRACT Sinusitis is an inflammation of the paranasal sinus mucosa, frequently accompanied by symptoms such as nasal congestion, excessive nasal discharge, sneezing, and headaches, particularly in the frontal region. The management of sinusitis can be conducted through both pharmacological and non-pharmacological approaches, including acupuncture therapy. Acupuncture is known to alleviate sinusitis symptoms by improving Qi circulation, reducing inflammation, and enhancing immune system function. This study aims to determine the benefits of acupuncture care for a client with sinusitis at